A Novel Decision-Making Approach to Fund Investments Based on Multigranulation Rough Set. (14th October 2018) - Yue, Xima; Su, Xiang
Abstract : Fund investment is a hot issue in today's society. How to choose a project for investment is affected by many factors. In view of this problem, this paper starts from the granular computing point of view and combines the multigranulation rough set decision-making method to construct a fund investment decision information system; then, the fund investment decision information system is reduced under different thresholds, and the decision rules are extracted through reduction. And from the aspects of decision accuracy and rule accuracy, the rules are analyzed. Finally, decision rules are used to give the decision of the fund investment project. This study provides a new approach to fund management.